Effects of Enterococcus faecium on Diet in the Dynamics of CD4+ and CD8+ Cell Infiltration in the Intestinal Mucosa of Broilers Challenged with Salmonella Minnesota - Kuritza, Leandro Nagae; Lourenco, Mariana Camargo; Miglino, Leonardo; Pickler, Larissa; Kraieski, Antonio Leonardo; Santin , Elizabeth (International Journal of Poultry Science, 2013)
The emergence of different Salmonella serovars raises concern about human and animal infection and measures of Salmonella control should be studied. The use of Enterococcus faecium (EF) as probiotic in poultry feed was studied to control Salmonella Minnesota (SM) infection in crop and cecum of SM challenged broilers and to assess its effect on immune cell infiltration into ileum and cecum mucosa of broilers. Birds were divided into three treatment groups: Negative control, birds non-inoculated; Positive control, with SM inoculated birds and Probiotic, with SM inoculated birds and treated with EF-containing diet. Before SM challenge, birds of the Probiotic group presented increased goblet cell counts in the ileum and cecum, decreased CD8+ cells in the ileum and increased CD4+ cells in the cecum as compared to birds from the Negative control. After SM challenge, birds from Probiotic group presented decreased Salmonella counts in cloacal swabs at 48 hours post-inoculation (p.i.) and also in the cecum and litter at 35 days of age. The CD4+cell in the ileum and CD8+cell counts in the cecum were lower when compared to the Positive control counts. Based on these results, it can be assumed that the use of EF probiotic can reduce Salmonella spp. counts and therefore affect CD4+ and CD8+ cells mobilization in the ileum and cecum mucosa of broilers.